Un objet lexicographique non identifié : le dictionnaire usuel des bionymes - Michèle Debrenne (Corela)
The paper presents the project of a new lexicographic tool, the “Common Multilingual Dictionary of Bionyms”, led by a team of Russian linguists. In this dictionary we collect not only spontan associations and comparisons given for a noun (meaning an animal or a plant), but also phrases with this word and a definitions. The paper exposes the initial stage of the project, which begun in 2013 and will allow to complete lexicographic descriptions made by professionals with the results of the metalinguistic activity of naïve language users.